Implementation Of Early Breastfeeding Initiationon In Ponre Public Health Centers - Kurniati, Ely; Muriyati; Asri (Lembaga Penelitian dan Pengabdian Masyarakat, Stikes Panrita Husada Bulukumba, 2017)
Early Breastfeeding Initiation starters early suckling infant is breastfed Individual Start Immediately taxable income of birth. How early breastfeeding initiation babies do best called crawling crawl for Breast Allow at least 60 minutes. Objective Namely be knew Overview Implementation of Early oBreastfeeding Initiation in ponre public health centers of gantarang districts bulukumba in may until june 2016 Research conducted in ponre public health centers of gantarang districts bulukumba in may until june 2016. It operates research is descriptive wiyh singer using primary data retrieved That Operates Directly From with samples using observation sheets, where a sample of 33 Term orangutan WITH Sampling technique using consecutiv That is all The sampling can be sampled Under Affordable provided And the requirements of a population sample. The result of the research indicate that of the research indicate that of the 33 total respondents, 9(27,27%) of them do early breastfeeding initiation accurately, 5 ( 15,15%) of them do it inaccurately and 19 (57,57%) respondents do not early breastfeeding initiation. Suggestion The midwife delivered the expected thing yet fully perform early breastfeeding initiation for the review would increase its service quality with actively attends trainings about the latest standard delivery assistance Additional early initiation of breastfeeding and Active educate mothers prenatal relates IN THE early breastfeeding initiation.